1999
DOI: 10.1097/00000539-199910000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Cytokine Responses During Coronary Artery Bypass Surgery: Specific Production of Interleukin-8 and Its Attenuation by Hypothermic Cardiopulmonary Bypass

Abstract: Using juguloarterial gradients to measure cerebrovascular cytokine production is novel in the setting of cardiopulmonary bypass and implicates the cerebral activation of inflammatory processes, which may contribute to brain dysfunction. Hypothermia during cardiopulmonary bypass may significantly attenuate this response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…37,41,[43][44][45] Hypothermia is thought to play a neuroprotective role after ROSC by decreasing metabolic demand, 46,47 decreasing the release of excitatory neurotransmitters, 16 and decreasing inflammation. 48 Animal studies since the 1980s [49][50][51][52][53][54][55][56][57] have suggested that mild induced hypothermia may be beneficial as a neuroprotectant after cardiac arrest. In addition, human literature describes a beneficial effect of mild induced hypothermia in resuscitated post cardiac arrest patients.…”
Section: Discussionmentioning
confidence: 99%
“…37,41,[43][44][45] Hypothermia is thought to play a neuroprotective role after ROSC by decreasing metabolic demand, 46,47 decreasing the release of excitatory neurotransmitters, 16 and decreasing inflammation. 48 Animal studies since the 1980s [49][50][51][52][53][54][55][56][57] have suggested that mild induced hypothermia may be beneficial as a neuroprotectant after cardiac arrest. In addition, human literature describes a beneficial effect of mild induced hypothermia in resuscitated post cardiac arrest patients.…”
Section: Discussionmentioning
confidence: 99%
“…None of these complications resulted in worsened outcome, and all were easy to manage. Although hypothermia is theorized to suppress immune response, 22 the rate of patients with pneumonia (5 of 9) was not higher than expected in comatose CA patients.…”
Section: Safetymentioning
confidence: 76%
“…The mechanism by which hypothermia conveys its neuroprotective effects is unclear, but hypothermia decreases metabolic demand, 20 decreases release of extracellular glutamate and other neurotoxic transmitters, 21 suppresses inflammation, 22 and stabilizes cell membranes. 23 To date, few preliminary reports have evaluated post-CA neuroprotective hypothermia in humans.…”
mentioning
confidence: 99%
“…31,32 Whether cerebral inflammatory processes occur as a result of CPB is not clear. 33,34 The common link between temperature and outcome might relate to an inflammatory process initiated during CPB that causes the brain injury and an independent hyperthermia, which then further exacerbates that injury. So in effect, this association that we have described may be both cause and effect.…”
Section: Discussionmentioning
confidence: 99%